On a class of nonlinear discrete problems of Kirchhoff type - BARGHOUTHE, Mohammed; AYOUJIL, Abdesslem; BERRAJAA, Mohammed (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
In view of variational methods and critical points theory, we study the existence of solutions for a discrete boundary value problem, which is a discrete variant of a continuous (p1(x), p2(x))-Kirchhoff-type problem, with a real parameter λ > 0. Mathematics Subject Classification (2010): 39A27, 35J25, 39A14, 35J58. Received 17 March 2025; Accepted 10 June 2025.